Contactless conductivity detection for analytical techniques—Developments from 2012 to 2014. Issue 1 (13th October 2014) - Kubáň, Pavel; Hauser, Peter C.; El Rassi, Ziad
<x xml:space="preserve">Abstract</x> The review covers the progress of capacitively coupled contactless conductivity detection over the 2 years leading up to mid‐2014. During this period many new applications for conventional CE as well as for microchip separation devices have been reported; prominent areas have been clinical, pharmaceutical, forensic, and food analyses. Further progress has been made in the development of field portable instrumentation based on CE with contactless conductivity detection. Several reports concern the combination with sample pretreatment techniques, in particular electrodriven extractions. Accounts of arrays of contactless conductivity detectors have appeared, which have been created for quite different tasks requiring spatially resolved information. The trend of the use of contactless conductivity measurements for applications other than CE has continued.